Case report: Long-term intracranial effect of zimberelimab monotherapy following surgical resection of high PD-L1-expressing brain metastases from NSCLC - Wu, Weijia; Guo, Jinyou; He, Lianxiang; Deng, Qi; Huang, Xianping (Frontiers in Oncology, 2024)
Non-small cell lung cancer (NSCLC) isaccounted for the second most prevalentmajority of lung cancer cases worldwide. Brain metastases (BM) frequently complicate NSCLC and portend a dismal prognosis. To control neurological symptoms, surgical resection is commonly followed by brain radiotherapy (RT). However, RT is often complicated by neurotoxicity. For patients with tumors that harbor positive driver genes, tyrosine kinase inhibitors are considered the standard of care. Nevertheless, treatment options for those without driver gene mutations are still debated. Programmed death receptor 1 (PD-1)/ligand 1 (PD-L1) inhibition has emerged as a novel therapeutic strategy for NSCLC patients with PD-L1-positive tumors, as well as for those with asymptomatic BM. However, the effect of anti-PD-1 antibodies on active BM within such specific populations is undetermined. Herein we present a case of a 65-year-old patient with NSCLC and high PD-L1-expressing BM. The patient underwent surgical resection of BM followed by firstline monotherapy with 31 cycles of zimberelimab, a novel anti-PD-1 antibody, and has already achieved 24 months of progression-free survival and intracranial recurrence-free survival. To our knowledge, this is the first report regarding the intracranial effect of zimberelimab on BM from primary lung cancer. This case report might facilitate an understanding of the intracranial effects of different anti-PD-1 antibodies for such populations in clinical practice.